Interference mitigation for coded MB-OFDM UWB - Snow, Chris; Lampe, Lutz; Schober, Robert (2008 IEEE Radio and Wireless Symposium, RWS, 2008)
We consider the ECMA-368 Multiband Orthogonal Frequency Division Multiplexing (MB-OFDM) standard for high rate Ultra Wideband (UWB) wireless communication in the 3.1-10.6 GHz band. The performance of MB-OFDM is impacted by interference from IEEE 802.16 WiMAX systems operating in the licensed 3.5 GHz band. Motivated by recent work showing the approximately Gaussian nature of the WiMAX interference to MB-OFDM, we propose a simple two-stage interference mitigation technique for coded MB-OFDM transmissions according to the ECMA-368 standard, consisting of interference spectrum estimation during silent periods followed by appropriate bit metric weighting during Viterbi decoding. We compare parametric and non-parametric spectrum estimation techniques for coded MB-OFDM transmissions and WiMAX interference for various scenarios of interest. The proposed two-stage interference mitigation technique is shown to be highly effective at mitigating the impact of WiMAX interference. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03